A PHYSICOCHEMICAL MODEL FOR DEEP DEGASSING OF WATER-RICH MAGMA - Maksimov A.P. (My University, 2008)
Two powerful eruptions of Quizapu vent on Cerro Azul Volcano, Chile are used as examples to discussthe problem of effusive eruptions of magmas having high preeruptive volatile concentrations. A physicochemicalmechanism is proposed for magma degassing, with the volatiles being lost before coming to the surface.The model is based on the interaction of magmas residing in chambers at different depths and on the differencebetween the solubility of water in the melt and the water equilibrium concentration in a magma bodyhaving a considerable vertical extent. The shallower chamber can accumulate the volatiles released from themagma that is supplied from the deeper chamber. An explanation is provided of the dramatic differences in thecharacter of the 1846–1847 and 1932 eruptions, which had identical chemical–petrographic magma compositions.
Keywords: 38.37.25 Вулканология; Авачинский; Сьерро-Ассуль (Чили)